Promoting health equity in European children: Design and methodology of the prospective EPHE (Epode for the Promotion of Health Equity) evaluation study - Mantziki, Krystallia (2014)
Background: Reducing health inequalities is a top priority of the public health agendas in Europe. The EPHE project aims to analyse the added value of a community-based interventional programme based on EPODE methodology, adapted for the reduction of socio-economic inequalities in childhood obesity. The interventions that will be implemented by this project focus on four energy balance-related behaviours (fruit and vegetable consumption, tap water intake, physical inactivity, sleep duration) and their determinants. This article presents the design of the effect evaluation of the EPHE project. Methods/Design: This is a prospective two-year follow-up evaluation study, which will collect data on the energy balance-related behaviours and potential environmental determinants of 6–8 year olds, depending on the socioeconomic status of the parents. For this purpose a parental self-reported questionnaire is constructed. This assesses the socio-economic status of the parents (5 items) and the dietary (12 items), sedentary (2 items) and sleeping (4 items) behaviour of the child. Alongside potential family-environmental determinants are assessed. The EPHE parental questionnaire will be disseminated in schools of a selected medium-sized city in seven European countries (Belgium, Bulgaria, France, Greece, Portugal, Romania, The Netherlands). Discussion: This study will evaluate the effects of the EPHE community-based interventional programmes. Furthermore, it will provide evidence for children’s specific energy balance-related behaviours and family environmental determinants related to socio-economic inequalities, in seven European countries.